2019
DOI: 10.1177/2333794x19865442
|View full text |Cite
|
Sign up to set email alerts
|

“What Will I Be Doing There Among So Many Women?”: Perceptions on Male Support in Prevention of Mother to Child Services in Lilongwe, Malawi

Abstract: Participation of males in the prevention of mother-to-child transmission (PMTCT) programs remains a challenge despite the implementation of guidelines. The study aimed at exploring male involvement in the PMTCT program at a primary health facility in Lilongwe, Malawi. Focus group discussions and in-depth individual interviews were used to collect data from health care workers, men, and women who were attending PMTCT services. Snowball sampling was used to recruit participants who were purposively identified. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 37 publications
(78 reference statements)
1
4
0
Order By: Relevance
“…The fear of marital dissolution as stated in this study is in line with the results from a previous study that reported that fear of stigma and relationship dissolution also influenced non-disclosure among couples [28]. Notably, women often associate disclosure of their HIV infected status with the dissolution of their relationship [31,45]. This may explain why one woman in our study reported that she planned to hide her HIV status and her ARV from the partner as she thought that disclosing would lead to the automatic dissolution of her relationship and accusations of promiscuity.…”
Section: Discussionsupporting
confidence: 91%
“…The fear of marital dissolution as stated in this study is in line with the results from a previous study that reported that fear of stigma and relationship dissolution also influenced non-disclosure among couples [28]. Notably, women often associate disclosure of their HIV infected status with the dissolution of their relationship [31,45]. This may explain why one woman in our study reported that she planned to hide her HIV status and her ARV from the partner as she thought that disclosing would lead to the automatic dissolution of her relationship and accusations of promiscuity.…”
Section: Discussionsupporting
confidence: 91%
“…Healthcare worker hostility was cited as the most common reason for male partners’ absence at delivery for pregnant women in North-Central Nigeria [ 87 ]. Strategies to accommodate male partners are important for their engagement and positive impact in maternal-child health [ 47 , 65 , 66 ]. These include making space and time for men’s health services and male peer support [ 47 , 88 ].…”
Section: Discussionmentioning
confidence: 99%
“…facilitate, but are not to participate in maternal-child healthcare, and women are to comply with measures found acceptable by male partners and/or the family/community to ensure the birth of a healthy baby [21, [64][65][66][67]. As a result, women who would otherwise access care may be unable to do so if their male partner is in disagreement, and men who desire to actively participate in maternal-child healthcare may be derided and stigmatized as non-masculine.…”
Section: Plos Onementioning
confidence: 99%
“…The area has several industrial companies such as tobacco, seed, plastic, and pharmaceutical companies. 16 …”
Section: Methodsmentioning
confidence: 99%
“…The area has several industrial companies such as tobacco, seed, plastic, and pharmaceutical companies. 16 Sampling A total of 30 participants were included in the study comprising 9 key informants and 21 clients. They were identified using a purposive sampling approach with maximum variation in mind to achieve a greater understanding of participants' experience (Table 1).…”
Section: Methodsmentioning
confidence: 99%